1996
DOI: 10.1136/thx.51.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hepatitis C virus infection in Italian patients with idiopathic pulmonary fibrosis.

Abstract: Background -A viral cause of idiopathic pulmonary fibrosis (IPF) was recently suggested by a Japanese study in which a high prevalence ofanti-hepatitis C virus (HCV) antibodies was detected. A subsequent British study failed to confirm these results. Methods -Antibodies to HCV were evaluated in 60 patients with IPF, 130 patients with non-interstitial lung disease, and in 4614 blood donors. HCV-RNA and HCV genotypes were evaluated in the anti-HCV positive patients with IPF. Anti-HCV antibodies were evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 11 publications
1
51
2
4
Order By: Relevance
“…A major concern, that has not been fully addressed, is the possibility that enhanced levels of some of these biomarkers can be found in IIPs as well as in malignancies, while these diseases may very well coincide. For example, an increased incidence of IPF has been reported in patients with hepatitis C virus (HCV) infection [73][74]. Arase et al reported increased levels of KL-6 one year before clinical onset of IPF in HCV patients [75].…”
Section: Discussionmentioning
confidence: 99%
“…A major concern, that has not been fully addressed, is the possibility that enhanced levels of some of these biomarkers can be found in IIPs as well as in malignancies, while these diseases may very well coincide. For example, an increased incidence of IPF has been reported in patients with hepatitis C virus (HCV) infection [73][74]. Arase et al reported increased levels of KL-6 one year before clinical onset of IPF in HCV patients [75].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis suggested that advancing age, smoking and liver cirrhosis were all independent risk factors for the development of IPF. However, a number of studies have failed to replicate this association [10] and some have simply demonstrated an association of HCV with a range of nonfibrotic respiratory conditions [11]. These differences between studies may reflect geographical variations in the incidence of HCV.…”
Section: Infection and The Pathogenesis Of Ipfmentioning
confidence: 99%
“…Conflicting studies on the incidence of HCV infection in patients with IPF have been published. Ueda et al [19] and Meliconi et al [20] reported a higher prevalence of HCV-antibody in patients with IPF compared with the general population. However, Irving et al [21] could not confirm the hypothesis that HCV may be a cause of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…HCV enhances pulmonary fibrosis 5881 cutanea tarda [9] , membranoproliferative glomerulonep hritis [12,13] , autoimmune thyroiditis [14][15][16] , sialadenitis [17] , and cardiomyopathy [18] . A few previous studies have presented conflicting results, with some suggesting that an incidence of anti-HCV antibody positivity in patients with idiopathic pulmonary fibrosis (IPF) is significantly higher than that in patients without IPF both in Italy and Japan [19,20] . Others found that incidence of anti-HCV antibody positivity is not high compared to controlled patients [21] .…”
Section: Introductionmentioning
confidence: 91%